Live birth rate following frozen–thawed blastocyst transfer is higher with blastocysts expanded on Day 5 than on Day 6. Issue 3 (31st January 2018) - Ferreux, Lucile; Bourdon, Mathilde; Sallem, Amira; Santulli, Pietro; Barraud-Lange, Virginie; Le Foll, Nathalie; Maignien, Chloé; Chapron, Charles; de Ziegler, Dominique; Wolf, Jean-Philippe; Pocate-Cheriet, Khaled
Abstract: STUDY QUESTION: The aim of this study was to evaluate the live birth rate (LBR) after frozen–thawed Day 5 (D5) and Day 6 (D6) blastocyst transfers. SUMMARY ANSWER: LBR following frozen–thawed blastocyst transfer is significantly lower with D6 than with D5 blastocyst regardless of embryo quality. WHAT IS KNOWN ALREADY: During fresh embryo transfer cycles, pregnancy rates (PR) are significantly higher when transferring blastocysts expanded on D5 compared with slow developing blastocysts (D6). In programmed thawed blastocyst transfer (TBT) cycles, the same clinical outcomes should be expected when transferring D5 or D6 blastocysts because of endometrial/embryonic synchronization due to hormonal priming of endometrial receptivity. However, the impact of delayed blastocyst expansion at D6 on clinical outcomes remains unclear. Some reports have shown higher PRs after D5 TBT compared with those of D6, while others have shown equivalent TBT outcomes after D5 and D6 cryopreserved blastocysts transfers. STUDY, DESIGN, SIZE, DURATION: This retrospective cohort follow-up study included 1347 single autologous frozen–thawed blastocyst transfers performed between January 2012 and December 2015 at a tertiary care university hospital. PARTICIPANTS/MATERIALS, SETTING, METHODS: All of the patients scheduled for TBT were allocated to two groups according to the day of blastocyst expansion: on D5 ( n = 994) or on D6 ( n = 353). The primary outcome was LBR per embryo transfer in the first blastocyst thawing cycle. Secondary outcomes were clinical pregnancy rate (cPR), early miscarriage rate and neonatal outcomes following TBT for the two groups. Statistical analyses were conducted using univariate and multivariate logistic regression model. MAIN RESULTS AND THE ROLE OF CHANCE: The LBR was significantly increased in the D5 group compared to the D6 group [294/994 (29.6%) versus 60/353 (17.0%); P < 0.001]. The cPR was also higher when blastocysts were vitrified on D5 compared with those vitrified on D6 [429/994 (43.2%) versus 95/353 (26.9%); P < 0.001]. No significant differences were found between groups in terms of early miscarriage rate ( P = 0.862). More good-quality embryos (defined as an B3–B4 or B5 embryo ≥BB according to the grading scale proposed by Gardner) were transferred in the D5 group than in the D6 group [807 (81.2%) versus 214 (60.6%); P < 0.001]. However, a comparison of TBT cycles with equal embryo quality (good versus low) also supported the superiority of D5 blastocysts. Concerning neonatal outcomes, the D5 group infants had a lower mean birth weight compared to those of the D6 group ( P = 0.001). In addition, a significantly shorter gestational age at birth is reported in the D5 blastocyst group as compared to the D6 group ( P = 0.004). After multivariate logistic regression taking into account potential confounders such as the women's age, number of previous IVF/ICSI procedures, the day of the blastocyst vitrification (D5 or D6) and embryo quality, blastocyst expansion at D6 was independently associated with a significant decrease in LBR compared to D5 expanded-blastocysts (OR 0.52; 95% CI 0.38–0.72; P < 0.001). LIMITATIONS, REASONS FOR CAUTION: The poor predictive value of the morphological approach in embryo selection could constitute a limitation in this study. However, blastocyst quality was evaluated similarly in both groups. WIDER IMPLICATIONS OF THE FINDINGS: The LBR following frozen–thawed blastocyst transfer was significantly lower with D6 than with D5 blastocysts, regardless of their quality. These results could affect cryopreservation procedures as they suggest that the use of D5-expanded blastocysts for TBT may be preferred in order to shorten the time of conceiving. STUDY FUNDING/COMPETING INTEREST(S): No specific funding was obtained for this study. None of the authors have any competing interests to declare. TRIAL REGISTRATION NUMBER: Not applicable.